Old origin for an European‐African amphitropical disjunction pattern: New insights from a case study on wingless darkling beetles - (:unkn) unknown (My University, 2022)
Aim: The origin of the amphitropic Mediterranean Basin and southern African disjunction (European-African amphitropical disjunction; EAAD) pattern is generally attributed to recent dispersal events. However, our knowledge is limited because the origin of the EAAD pattern has been almost exclusively studied in plants. Here, we investigate the origin of this wide-ranging disjunction pattern in a group of wingless insects, consisting of two major clades, both of which have EAAD distributions. Location Sub-Saharan Africa and Mediterranean region. Taxon Tribe Dendarini (Coleoptera: Tenebrionidae). Methods: We reconstructed a dated molecular phylogeny of major lineages within Dendarini using maximum likelihood and Bayesian inference. The employed dataset included sequences of six genes (two mitochondrial and four nuclear fragments) generated for 72 species. To investigate the sequence and timing leading to present-day wide-ranging disjunction patterns, we conducted parametric historical biogeography analyses. Results: The dated phylogenetic framework supports the monophyly of all major Dendarini lineages and highlights the origin of the tribe in sub-Saharan Africa during the Middle Eocene. From there, representatives of the two major lineages colonized the Mediterranean region at the Oligocene-Miocene boundary, with one lineage first reaching North Africa, whilst the other reached southern Europe. Main conclusions: The origin of the EAAD in Dendarini beetles is ancient and better explained by the progressive fragmentation of the pan-African rainforest that started in the Early Eocene than by other scenarios. This and the increased aridification associated with the global long-term cooling trend that took place at that time had a strong influence on the diversification and distribution of xerophilic organisms such as dendarine beetles. This challenges the understanding of the origin of EAAD patterns, highlighting that they do not only result from recent dispe
Keywords: African Research